GAMBARAN PENGETAHUAN IBU TERHADAP DIARE AKUT BALITA DI RSUD ARIFIN ACHMAD PROVINSI RIAU DAN PUSKESMAS RAWAT INAP PEKANBARU - Dwiriyanti H, Dhita Natasha; Savira, Maya; ", Suyanto (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTDiarrhea is the most cases that has increased morbidity and mortality, especially children under five year. Diarrhe was the second largest after pneumonia disease. Diarrhea disease in Indonesia is a major cause of infant mortality is approximately 31.4% and 25.2% in children under five years. Riau is a province that has a prevalence rate of diarrhea above the national average. There are several causes of diarrhea and for developing countries such as Indonesia the majority caused by infection. Infection can be derived from environmental factors, especially the children and mothers who are less hygienic. Diarrhea in children require extra attention because more than 70 % of the body of water and likely to fall to dehydration of the weight and the role of mother to know and take care of diarrhoea in the house is very necessary. This study will show reveal the mother's knowledge towards acute diarrhea in toddler. This research was a descriptive prospective with cross-sectional approach. This study used interviews and questionnaire instruments about knowledge of the mother. These samples included 105 respondents from Riau Province Arifin Achmad Hospital and Health Center Inpatient Pekanbaru. The results showed that both the mother's knowledge as much as 67 mothers (63.8%), quite as much as 24 mothers (22.9%) and who have less knowledge as much as 14 mothers (13.3%).Keywords: Diarrhea, morbidity, mortality, knowledge, cross-sectional